Research in social movements, conflicts and change. Vol. 28 (Emerald Group, 2008)
Social movement strategies and coalition dynamics in movements are two of the hottest arenas for cutting-edge research. Many case studies offer useful analytical windows through which we can understand the strategic choices made by individual movement organizations. Equally if not more important questions remain about how the positions a movement organization occupies in the broader social movement field impacts strategic decision-making. Coalition politics and conflicts matter to social movements.Thus Section One of this volume of "Research in Social Movements, Conflicts and Change" presents a series of papers focused on the complex dynamics of coalitions and the interorganizational relations within social movements. Another section follows immediately that compliments in an integrated way the first, this one focused on strategic decision making in social movements, including with regard to strategic alliances. The Volume closes with a third section on political opportunities and political inequalities. This volume of the "Research in Social Movements, Conflicts and Change" does what the series has always done best: showcase sound empirical work and creative theory-building that addresses those questions currently at the forefront of the field.